2012
DOI: 10.1371/journal.pone.0042410
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional Analysis of Clinically Relevant Heat Stress Response in Clostridium difficile Strain 630

Abstract: Clostridium difficile is considered to be one of the most important causes of health care-associated infections worldwide. In order to understand more fully the adaptive response of the organism to stressful conditions, we examined transcriptional changes resulting from a clinically relevant heat stress (41°C versus 37°C) in C. difficile strain 630 and identified 341 differentially expressed genes encompassing multiple cellular functional categories. While the transcriptome was relatively resilient to the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 62 publications
8
44
0
Order By: Relevance
“…Previous studies have shown that in Clostridium difficile strain 630, the flagellin gene ( fliC ) will be down-regulated in response to heat shock (Ternan et al, 2012). Contrary to this finding, salt stress triggered a significant increase in the clostridial transcript abundance related to flagellar synthesis (3.4 log 2 fold) and motility (4.8 log 2 fold) at 600 mM NaCl ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that in Clostridium difficile strain 630, the flagellin gene ( fliC ) will be down-regulated in response to heat shock (Ternan et al, 2012). Contrary to this finding, salt stress triggered a significant increase in the clostridial transcript abundance related to flagellar synthesis (3.4 log 2 fold) and motility (4.8 log 2 fold) at 600 mM NaCl ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hfq inactivation is frequently associated with increased sensitivity to various stresses in bacteria (14,17). In C. difficile, the global response to several environmental (temperature, pH, and oxygen) and antibiotic stresses that bacteria could encounter in the gut has been recently studied by a transcriptome approach (63,64,82). Interestingly, several genes encoding cell wall proteins and membrane transporters or having involvement in various metabolic pathways that are differentially expressed in the Hfq-depleted strain are induced by acid, alkali pH, heat shock, and the presence of subinhibitory concentrations of amoxicillin or clindamycin antibiotic (63) (see Table S4 in the supplemental material).…”
Section: Discussionmentioning
confidence: 99%
“…This included several genes probably in- During host infection, C. difficile is exposed to several stresses and responds to stress stimuli by inducing different mechanisms of defense (62). Among stress-related genes, we observed about 2-fold upregulation of genes encoding heat shock proteins, including groEL (CD0194) and grpE (CD2462) that are induced by clinically relevant heat stress and acid pH conditions in C. difficile (63,64) and by metabolic stresses in Clostridium acetobutylicum (65). Moreover, the expression of several genes that might be involved in the oxygen tolerance response and cell redox balance was altered in the CDIP53 strain compared to the CDIP51 strain.…”
Section: Construction Of a Strain Depleted For Hfq And Analysis Of Itmentioning
confidence: 92%
“…In support of this, CD3068 was down regulated some 1.9-fold by microarray, as indeed was CD3069, the IId component at 2.2-fold down [42]. In the combined proteome, the EI component (CD2755), common to, and essential for all phosphotransferase systems in the cell, was down regulated by 3.9 fold, although transcripts were reduced by only 1.46 fold [42].…”
Section: Resultsmentioning
confidence: 64%
“…Interestingly, the CD2532 transcript does not change significantly under heat stress as revealed by both microarray and qRT-PCR analysis [42]. CD2531 and CD2532 are predicted to generate a bicistronic messenger and indeed the transcript for CD2531 was also unchanged [42].…”
Section: Resultsmentioning
confidence: 96%